2000
DOI: 10.1161/01.hyp.35.2.637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Brachial Artery Wall Properties Differs From the Aorta and Is Gender Dependent

Abstract: Abstract-Compliance and distensibility are wall properties of large arteries, which may play a role in cardiovascular disease. The purpose of this study was to investigate whether the influence of age on these vessel wall properties differs between vascular territories and is gender-dependent. In a population sample of 498 men and women 20 to 79 years of age, diameter, distensibility, and compliance coefficient of the muscular brachial artery were measured with an echo-tracking device. Distensibility of the ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
196
4
10

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(230 citation statements)
references
References 37 publications
20
196
4
10
Order By: Relevance
“…8,19 This technique gives a reliable index of the regional AoStiff, 28,29 but represents only an estimate of the local AoStiff because it is a summation of the individual biomechanical properties of different arterial walls (that is, carotid, aorta, iliac and femoral arteries) located between the two recording sites. 30,31 Our data showed that IWV measurements are highly correlated with the carotid-femoral PWV, indicating that IWV also provides a reliable estimate of the regional AoStiff (see Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 58%
“…8,19 This technique gives a reliable index of the regional AoStiff, 28,29 but represents only an estimate of the local AoStiff because it is a summation of the individual biomechanical properties of different arterial walls (that is, carotid, aorta, iliac and femoral arteries) located between the two recording sites. 30,31 Our data showed that IWV measurements are highly correlated with the carotid-femoral PWV, indicating that IWV also provides a reliable estimate of the regional AoStiff (see Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 58%
“…This is important, because there are marked differences between muscular and elastic arteries with respect to aging and the association between stiffness and cardiovascular risk. 5,19 Muscular arteries show little increase in stiffness with age in contrast to elastic arteries. 20 Age-related stiffening of elastic arteries, particularly the aorta, is accelerated in the presence of risk factors for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…We invited the subjects enrolled in our longitudinal study 4 for an extensive evaluation of the structural and functional properties of their large arteries. 5 We report in this article our findings with regard to menopause.…”
Section: Introductionmentioning
confidence: 86%